THE COMPLIANCE OF TURKSOY WITH GOVERNANCE PRINCIPLES: A QUALITATIVE EVALUATION (Third Sector Social Economic Review, 2021)
In the globalizing World, the concept of governance is one of the concepts most extensively dealt with in a globalizing world. Indeed, governance offers various solutions as the world goes through various economic crisis and faces serious challenges brought about by increased instability, hence the growing importance of governance. The international organization which this paper deals with as an example uses/applies the concept of governance for different purposes. In this respect, comprehensive interviews and written consultation have been carried out in order to evaluate TURKSOY in terms of good governance.  Data obtained as a result of thereof show that TURKSOY is transparent towards its member countries and that while none of the latter is superior to one another, decisions are made on a joint basis. Indeed, the organization publishes its yearly activity reports which are accessible to the large public. As TURKSOY and its activities have a diplomatic status, modalities regulating the auditing and inspection thereof are determined in its statutes. However, in practice, it has been observed that upon request of the organization an inspection has annually been carried out once a year either by the Auditing Board of the related Ministry or by independent auditing companies. The afore-mentioned research has further shown that the rule of law which is one of the underlying principles of good governance is also being widely respected.
Keywords: Governance; Principles; TURKSOY